A brief history of the Harvest experiment: 1989–2019. Issue 2 (15th July 2021) - Haines, Bruce; Desai, Shailen D.; Kubitschek, Daniel; Leben, Robert R.
Abstract: The Harvest Oil Platform, near Point Conception, California, has long served as the NASA prime verification site for the TOPEX/POSEIDON and Jason series of reference altimeter missions. In this brief review article, we provide a short history of the platform verification experiment dating to the site selection in 1989. We describe the evolution of the verification data record over the past three decades, and demonstrate how the results have informed the development of a stable and accurate climate data record of sea level change from satellite altimetry.